Administrative and financial jurisdiction of provincial councils - Dana Abdel Karim Saeed; Saleh Tawfiq Hama Rashid (The Scientific Journal of Cihan University– Sulaimaniya, 2018)
The Kurdistan legislator adopted the system of regional administrative decentralization (local administration) to manage the provinces of the region through the legislation of the provincial law for the Kurdistan Region - Iraq No. 3 of 2009, which is currently in force. This law has been concerned with the provincial councils as the cornerstone for the establishment of this system at the provincial level, the administrative and financial aspects of the administrative and financial affairs to enable it to manage the affairs of the provinces in accordance with the principle of administrative decentralization in order to facilitate and improve the delivery of public services Citizens. In this research, we have tried to shed light on the administrative and financial competencies granted to the provincial councils within the Kurdistan Region of Iraq Law No. 3 of 2009, considering that the independence and effectiveness of these councils depends on the size and quality of these jurisdictions and the size of the financial resources allocated to them. In our research, we relied on the analytical and comparative approach, with the aim of clarifying these terms of reference and these resources, and indicating the imbalances and shortcomings. The research concluded with the most important conclusions and suggestions we reached during our study of the subject.